2015
DOI: 10.2196/jmir.3399
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Health Promotion Program for Older Workers: Randomized Controlled Trial

Abstract: BackgroundRecent evidence supports the efficacy of programs that promote improvements in the health practices of workers 50 years and older who are at higher risk for chronic diseases than younger workers are. Internet-based programs that promote healthy practices have also shown promise and, therefore, should be especially appropriate for workers aged 50 years and older.ObjectiveThe purpose of the research was to evaluate the effectiveness of HealthyPast50, a fully automated Web-based health promotion program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(177 citation statements)
references
References 36 publications
3
171
0
2
Order By: Relevance
“…Upon completion of the intervention, participants showed improvement on most selected health outcomes associated with calcium intake and exercise (Nahm et al, 2010). Other investigators also assessed the impact of a social cognitive theory (SCT)–based online health-promotion program among older workers ( n = 278; age = 50-59, 69%; Cook, Hersch, Schlossberg, & Leaf, 2015). The program was a media-rich (e.g., videos and pictures) website that included learning content on major health topics, including healthy aging, diet, and physical activity.…”
Section: Research On Online Health Interventions In Older Adultsmentioning
confidence: 99%
“…Upon completion of the intervention, participants showed improvement on most selected health outcomes associated with calcium intake and exercise (Nahm et al, 2010). Other investigators also assessed the impact of a social cognitive theory (SCT)–based online health-promotion program among older workers ( n = 278; age = 50-59, 69%; Cook, Hersch, Schlossberg, & Leaf, 2015). The program was a media-rich (e.g., videos and pictures) website that included learning content on major health topics, including healthy aging, diet, and physical activity.…”
Section: Research On Online Health Interventions In Older Adultsmentioning
confidence: 99%
“…All four studies were considered to contain serious risk of bias and of low methodological quality. Two randomized control trials were conducted and reported no impact of a web-based intervention on worker mental health compared with controls 56 , 57) . Two web-based health promotion programs ( COACH and RealAge ) for older workers were also evaluated through a cluster RCT 58) .…”
Section: Resultsmentioning
confidence: 99%
“…Five interventions 26 , 27 , 43 , 56 , 57) that referenced social cognitive theory (SCT) were also identified, including one that delivered SIT on mobile devices to oncology nurses 43) . SIT derives from the work of Meichenbaum 67 , 68) and encompassed three phases.…”
Section: Discussionmentioning
confidence: 99%
“…In synthesising the latest updates, Lattanzio et al (20) highlight three main domains of development related to advances in technological innovation to support care: 1) disease management; 2) intelligent devices to improve autonomous living and mobility in older persons; and 3) specific needs for active aging. Among common e-Health interventions in support of HA, some are designed for virtual physical exercise (21)(22), others promote networking (23), an active lifestyle (24) or independence (25). Interestingly, recent studies contend a high intention to adopt e-Health interventions among older adults (26) and recognize these interventions to be relevant, adapted and safe to use by these older users (27)(28)(29)(30).…”
Section: Among Interventions Dedicated To Maintain and Improve Older mentioning
confidence: 99%